PENGARUH PEMBELAJARAN SENI TERHADAP PERKEMBANGAN KREATIVITAS ANAK SEKOLAH DASAR - Yulia Sari Angraini; Farida Mayar; Desyandr (STKIP Subang, 2023)
Art learning has been introduced at the elementary school level where it is known as the SBDP subject. SBDP learning is very influential on children's development, especially in the development of creativity. Which SBDP learning aims to channel the creative ideas and imagination they have for a work. This study uses a Literature review research design. The data collection technique is by searching for literature from several previous studies related to the influence of art learning on the development of creativity in elementary school children where the tools for collecting data are using Google Scholar and the Ministry of Education and Culture's sinta. The results of this study indicate that there is an influence of art learning on the creativity development of elementary school children.